Larval morphology of three species of Anteoninae (Hymenoptera, Dryinidae) - Guglielmino, Adalgisa; Olmi, Massimo; Marletta, Alessandro; Bückle, Christoph (Zootaxa, 2017)
The last immature stage and the mature larva of Anteon flavicorne (Dalman) and Lonchodryinus ruficornis (Dalman) (Dryinidae, Anteoninae) are described. Figures and descriptions of some characters of the exuvia of the mature larva of Deinodryinus hispanicus (Olmi) are added. The immature larvae of the studied species are characterized by a layer (“mask”) covering the frontal region, the absence of cephalic vesicles, the body with its posterior region strongly bent ventrally, and the position on the host always on the thorax or between metathorax and abdomen. Main features of the mature larvae are the very long setae on the body and head, the labrum with few long sensory bristles and two sensory pits and with an apical row of sensory bristles, the epipharynx with two sensilla, the subtriangular labium with narrow subquadrate spinneret, and the bulb-shaped spiracles of approximately equal size in thorax and abdomen. The cocoon is built in the ground and covered by soil particles.